Impact of cordon-bleu expression on actin cytoskeleton architecture and dynamics - Grega-Larson, Nathan E. (Cytoskeleton (Hoboken), 2016)
Cordon-bleu (COBL) is a multifunctional WASP-Homology 2 (WH2) domain-containing protein implicated in a wide variety of cellular functions ranging from dendritic arborization in neurons to the assembly of microvilli on the surface of transporting epithelial cells. In vitro biochemical studies suggest that COBL is capable of nucleating and severing actin filaments, among other activities. How the multiple activities of COBL observed in vitro contribute to its function in cells remains unclear. Here, we used live imaging to evaluate the impact of COBL expression on the actin cytoskeleton in cultured cells. We found that COBL induces the formation of dynamic linear actin structures throughout the cytosol. We also found that stabilizing these dynamic structures with the parallel actin bundling protein espin slows down their turnover and enables the robust formation of self-supported protrusions on the dorsal cell surface. Super-resolution imaging revealed a global remodeling of the actin cytoskeleton in cells expressing these two factors. Taken together, these results provide insight as to how COBL contributes to the assembly of actin-based structures such as epithelial microvilli.